Hormonal contraception increases risk of asthma among obese but decreases it among nonobese subjects: a prospective, population-based cohort study - Melanie C. Matheson; John A. Burgess; Melisa Y.Z. Lau; Adrian J. Lowe; Lyle C. Gurrin; John L. Hopper; Graham G. Giles; David P. Johns; E. Haydn Walters; Michael J. Abramson; Francisco Gómez Real; Shyamali C. Dharmage (ERJ Open Research, 2015)
Epidemiological data on asthma suggest a sex difference that varies with age. Hormonal effects have been suggested as a possible explanation for these differences but there is a scarcity of evidence on these relationships. Our objective was to examine the relationship between reproductive factors and asthma risk among females and to examine whether body mass index (BMI) modifies this relationship. Female participants in the 2004 fifth decade follow-up postal survey of the Tasmanian Longitudinal Health Study formed the study population. Reproductive history and data on hormonal contraceptive (HC) use were collected on 2764 females. Multiple logistic regression was used to assess the association between the reproductive factors and current asthma. The mean age of participants was 43 years and the prevalence of middle-aged current asthma was 12.8%. Females with very early menarche (≤10 years) had higher odds of middle-aged current asthma (OR 1.91, 95% CI 1.14–3.2). Pregnancy history (number of births and age at first pregnancy) were not associated with current asthma risk at 44 years. Ever having used HCs, years of use and age started using HCs were not individually associated with current asthma risk. However, body mass index significantly modified the relationship between HC use and asthma. We found increasing years of pill use was associated with a significantly increased risk of current asthma in overweight/obese women but a reduced risk in normal weight women (interaction p=0.015). Hormonal effects from use of HCs and early menarche may contribute to the sex differential in asthma risk. Our findings suggest that in obese women with a history of long-term HC use may be at an increased risk of chronic respiratory disease, and regular monitoring for asthma and asthma symptoms may be recommended.